Migrant entrepreneurs and credit constraints under labour market discrimination - Paul Frijters; Tao Kong; Xin Meng (Institute for the Study of Labor (IZA), 2011)
We use a unique data of representative migrants and urban local workers in 15 Chinese cities to investigate entrepreneurship and credit constraints under labour market discrimination. We divide self employed into prefer to be self-employed and prefer to have a salaried job but cannot find one; and divide salaried workers into want-to-be entrepreneurs and happy-to-be salaried workers. Over 40 percent of migrant workers are either currently or want-to-be entrepreneurs. Both groups are very similar in terms of risk taking preferences and network size. Want-to-be entrepreneurs however suffer from credit constraints identified by negative financial shocks in the year before. Our back-of-envelope calculation reveals that overcoming the current level of credit constraints may be worth 2% of GDP per year direct earnings increases.
urn:nbn:de:101:1-201110053418
Keywords: L26; J14; J70; 330; entrepreneurs; credit constraints; migration; China; Migranten; Unternehmer; Selbstständige; Verschuldungsrestriktion; Arbeitsmarktdiskriminierung; China